2014
DOI: 10.2967/jnumed.114.139428
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-Density Lipoprotein Stimulates Macrophage 18F-FDG Uptake via Hypoxia-Inducible Factor-1α Activation Through Nox2-Dependent Reactive Oxygen Species Generation

Abstract: For 18 F-FDG PET to be widely used to monitor atherosclerosis progression and therapeutic response, it is crucial to better understand how macrophage glucose metabolism is influenced by the atherosclerotic microenvironment and to elucidate the molecular mechanisms of this response. Oxidized low-density lipoprotein (oxLDL) is a key player in atherosclerotic inflammation that promotes macrophage recruitment, activation, and foam cell formation. We thus explored the effect of oxLDL on macrophage 18 F-FDG uptake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 38 publications
4
46
0
Order By: Relevance
“…Macrophages have the capacity to effectively switch to glycolysis after exposure to hypoxia (14,17), bacterial products (9,13), or in response to certain other proinflammatory stimuli (eg, modified lipoproteins) (12,15). However, macrophages can efficiently use oxidative metabolism after exposure to the anti-inflammatory cytokine interleukin-4 to support their bioenergetic and metabolic needs (9,28).…”
Section: Experimental Studies: Regulation Of Macrophage Glucose Metabmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages have the capacity to effectively switch to glycolysis after exposure to hypoxia (14,17), bacterial products (9,13), or in response to certain other proinflammatory stimuli (eg, modified lipoproteins) (12,15). However, macrophages can efficiently use oxidative metabolism after exposure to the anti-inflammatory cytokine interleukin-4 to support their bioenergetic and metabolic needs (9,28).…”
Section: Experimental Studies: Regulation Of Macrophage Glucose Metabmentioning
confidence: 99%
“…Local production of M-CSF promotes the survival of foam cells and contributes to development of the early-stage, but not late-stage, atherosclerotic lesions (20,21 F-FDG PET studies (8)(9)(10)(11)(12)(13)(14). For example, glucose uptake and glycolysis are induced by bacterial-derived products, such as lipopolysaccharide (13), modified low-density lipoprotein (15,16), or hypoxia (17). However, the link between a proinflammatory macrophage phenotype and enhanced glucose uptake may be valid for only a number of stimuli and does not represent a universal phenomenon (9,14).…”
Section: Experimental Studies: Regulation Of Macrophage Glucose Metabmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have shown that HIF-1α played an essential role in the function of macrophages when challenged by ox-LDL and promoted the transformation of macrophages to foam cells (22,23). In leucocytes, which function as a key factor in the development and progression of atherosclerotic lesions, HIF-1α has been reported to have a direct effect on the cytokine profile (24).…”
Section: Discussionmentioning
confidence: 99%
“…One study assessed 18-FDG uptake vs. histology (r = 0.521, p = 0.003) [32] and showed that the SUV was signifi cantly higher in symptomatic (1.75) vs. asymptomatic (1.43) patients. Oxidized (ox) LDL has been shown to increase F-18-FDG uptake and glycolytic metabolism by more than an order of magnitude via the upregulation of GLUT1 expression and hexokinase activity [33,34]. Furthermore, proinfl ammatory cytokines [35,36], interferon, monocyte colony stimulating factor and lipopolysaccharides [37] are signifi cant stimulators of FDG uptake in macrophages.…”
Section: F-18-fdg Uptake At the Cellular Levelmentioning
confidence: 99%